2016
DOI: 10.3892/br.2016.580
|View full text |Cite
|
Sign up to set email alerts
|

Pleckstrin homology-like domain, family A, member 1 (PHLDA1) and cancer

Abstract: Abstract. Pleckstrin homology-like domain, family A, member 1 (PHLDA1) encodes a member of an evolutionarily conserved pleckstrin homology-related domain protein family. It was first identified as a potential transcription factor required for Fas expression and activation-induced apoptosis in mouse T cell hybridomas. The exact molecular and biological functions of PHLDA1 remain to be elucidated. However, its expression is induced by a variety of external stimuli and there is evidence that it may function as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 45 publications
(75 reference statements)
4
61
0
1
Order By: Relevance
“…PHLDA1 has 2 plextrin homology domains and polyglutamine domains suggestive of being a transcription factor [49]. Phlda1 is expressed in a wide variety of tissues and is found in different cellular compartments, including the nucleus, cytoplasm and endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PHLDA1 has 2 plextrin homology domains and polyglutamine domains suggestive of being a transcription factor [49]. Phlda1 is expressed in a wide variety of tissues and is found in different cellular compartments, including the nucleus, cytoplasm and endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact biochemical role and mechanism of action of PHLDA1 is poorly elucidated. Phlda1 appears to influence apoptosis and proliferation in cancer, but in a complex and tissue-specific manner [49], [50], [51]. For example, Phlda1 expression is reduced in melanoma and breast cancer but expressed at high levels in colon cancer and osteosarcomas [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PHLDA1 was first identified in the context of regulating T-cell apoptosis by inducing Fas expression, and was thus further named as T-cell death associated gene 51 [8]. Subsequent research showed that PHILDA1 plays crucial roles in cell proliferation and apoptosis, which affect cell survival and the development of various cancers, including melanoma, osteosarcoma, breast cancer, colon cancer, intestinal cancer, and gastric cancer [9]. Johnson and colleagues showed that PHLDA1 inhibited cell growth and colony formation, promoted apoptosis, and enhanced the sensitivity of melanoma cells to chemotherapeutic agents, suggesting that its expression may be involved in deregulated cell growth and apoptosis resistance in melanomas [10].…”
Section: Introductionmentioning
confidence: 99%
“…A relação de PHLDA1 com câncer já foi descrita em diferentes tipos tumorais, incluindo câncer de mama (Nagai et al 2007;Marchiori et al 2008;Oberst et al 2008;Johnson et al 2011;Li et al 2014;Kastrati et al 2014;Moad et al 2013;Nagai 2016), melanoma (Neef et al 2002), câncer de pulmão (Joo et al 2007), câncer colorretal (Chiu 2005), câncer renal (Tavares et al 2008) e carcinoma oral (Coutinho-Camillo et al 2013). …”
Section: Phlda1 E Câncer De Mamaunclassified